Caenorhabditis elegans Intersectin: A Synaptic Protein Regulating Neurotransmission - Rose, Simon (The American Society for Cell Biology, 2007)
Intersectin is a multifunctional protein that interacts with components of the endocytic and exocytic pathways, and it is also involved in the control of actin dynamics. Drosophila intersectin is required for viability, synaptic development, and synaptic vesicle recycling. Here, we report the characterization of intersectin function in Caenorhabditis elegans. Nematode intersectin (ITSN-1) is expressed in the nervous system, and it is enriched in presynaptic regions. The C. elegans intersectin gene (itsn-1) is nonessential for viability. In addition, itsn-1-null worms do not display any evident phenotype, under physiological conditions. However, they display aldicarb-hypersensitivity, compatible with a negative regulatory role of ITSN-1 on neurotransmission. ITSN-1 physically interacts with dynamin and EHS-1, two proteins involved in synaptic vesicle recycling. We have previously shown that EHS-1 is a positive modulator of synaptic vesicle recycling in the nematode, likely through modulation of dynamin or dynamin-controlled pathways. Here, we show that ITSN-1 and EHS-1 have opposite effects on aldicarb sensitivity, and on dynamin-dependent phenotypes. Thus, the sum of our results identifies dynamin, or a dynamin-controlled pathway, as a potential target for the negative regulatory role of ITSN-1.